(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The information about the research results of the polymorphic regions of chloroplast genomes of 4 endemic species from Scorpiris subgenera, namely Juno austrotschatkalica Tojibaev, F. Karim, et Turgunov, Juno pseudocapnoides Rukšāns, Juno victoris (F.O. Khass., Khuzhan. and Rakhimova) M.B. Crespo, Mart.-Azorín and Mavrodiev and Iris hippolyti (Vved.) Kamelin, is presented in this article. The research aimed to detect the most variable regions to use for specific primer design.